BENTUK KOMUNIKASI GURU DENGAN SISWA SLOW LEARNER DALAM PEMBELAJARAN: Studi Kasus Siswa Slow Learner SMP Budi Waluyo Jakarta - Rindiani, Desma Eka; Safitri, Desy (Edukasi IPS, 2018)
This research aims to know how the form of communication to overcome constraints vocabulary on the slow learner students in learning, the communication barriers in learning, as well as efforts by the teacher so that the learning was communicative in SMP Budi Waluyo South Jakarta class VIII. This research uses qualitative methods with the technique of data collection in the form of the technique of observation, interview, and documentation. Analysis of the data using the model of Miles and Huberman. The results of this research is verbal communication consists of oral elements with the Bible every day without language, the connotation and scientific, while writing with notes and memos that required schools. Nonverbal using the expression on his face when happy sad, anger, fear, shame, and interested in a matter. Movement of the body as to explain a form of objects, pointed toward the, reveals what difficult students say. While the touch of namely taps the shoulder to make students focus back on the lessons, touching the head and shoulders when it is advised, embrace and appoint if asked the students to be active to the front of the class. In learning found the communication barriers that there are in themselves the students are often dreaming in learning, less confident and less interested in the lessons according to the students difficult. The obstacles that there are from outside of the students such as the election of the appropriate words with the ability of students and the lack of facilities to support the lesson. Teachers attempt to create the learning atmosphere communicative through the question & answer, and make a game of learning. Using a simple learning media and multimedia like bringing the novel, music, appliance painting, pictures and videos learning, singing by changing the lyrics to matter and samosa, funny language learning. And give the touch of compassion as motivation and advice.